The Analytic Model of Consent and The Square of Opposition - Papageorgiou, Konstantinos (Conatus - Journal of Philosophy, 2019)
Modelling consent is a process prior to any discussion about it, be it theoretical or practical. Here, after examining consent, I shall attempt to present a “logical generator” that produces all different cases of consent (and/or of non-consent), so that afterwards we may articulate a two-dimensional model which will enable us to coherently demonstrate all possible types of consent. The resulting model will be combined with Aristotle’s square of opposition, offering us even greater insight. I shall claim that full(y) informed consent is an archetype, not realized in most cases; it is just one case out of hundreds more. I shall conclude with an educational model for consent, the principle of specificity, arguing that if we wish to both understanding consent and become more adept in exercising it, we need a targeted educational system – not just “better education” in general.